POLA PEMBERIAN ASI PADA BAYI IMD DI KELURAHAN SUBULUSSALAM KOTA KECAMATAN SIMPANG KIRI KOTA SUBULUSSALAM TAHUN 2012 - hikmah nurmaralita (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
The study is a descriptive survey using cross sectional design. The samples was all mothers who have babies that have been done early initiation of breasfeeding and when the study, baby’s aged 6-11 months. This study aims to know the description of breastfeeding patterns to babies who ha d done ​​an early initiation of breastfeeding in Subulussalam village, Simpang Kiri subregency of Subulussalam city. Data of breastfeeding pattern, knowledge and attitude about exclusive breastfeeding were collected by direct interview using questionnaire. Assessment of nutritional status carried out by measuring weight and length of the baby's then viewed by the standards of WHO Anthro 2005.The result of study showed that majority of mother’s (56,3%) breastfed ≥8 times a day when babies aged 0-6 months and at the age of 6-11 months most of mothers (84,4%) breastfed <8 times a day. 78,1% mothers feeding by alternating right and left breast.The majority of long breastfeeding is 5-15 minutes(55,6%) and 56,2% babies have been given solid food at age 1-2 month. Although it made an early initiation of breastfeeding, but only one mother (3.1%) who exclusively breastfed baby’s. Much as 59.4% of mothers are knowladge rate is moderate and 81,3% mothers attitude of exclusice breastfeeding is only moderate. 78,1% nutritional status of babies in the category of good/ normal are seen by BB/PB. Keywords: Alphabreastfeeding patterns,  early initiation of  breastfeeding’s baby